Implementation of Resource Discovery Mechanisms onto PeerSim - Azrul Amri, Jamal; Azwa, Abdul Aziz; Mohd Fadzil, Abdul Kadir; Wan Suryani, Wan Awang (2014)
Resource discovery is an important part of distributed computing and resource sharing systems, like grids and utility computing. The role of resource discovery is extremely important for peer-to-peer (P2P) systems. However, many researchers fail to list down how the implementation and tests on P2P simulator have been done. This paper discusses the implementation of resource discovery techniques such as random walk (RW), restricted random walk (RRW), breadth-first search (BFS), intelligent BFS (Int-BFS), depth-first Search (DFS), adaptive probabilistic search (APS), and blackboard resource discovery mechanism (BRDM) onto PeerSim, a P2P network simulator that is able to simulate large P2P environment. Brief information about each resource discovery techniques that are implemented onto PeerSim are discussed and presented